2010
DOI: 10.1111/j.1750-3841.2010.01788.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging (MRI) and Relaxation Spectrum Analysis as Methods to Investigate Swelling in Whey Protein Gels

Abstract: Effective means for controlled delivery of nutrients and nutraceuticals are needed. Whey protein-based gels, as a model system and as a potential delivery system, exhibit pH-dependent swelling when placed in aqueous solutions. Understanding the physics that govern gel swelling is thus important when designing gel-based delivery platforms. The extent of swelling over time was monitored gravimetrically. In addition to gravimetric measurements, magnetic resonance imaging (MRI) a real-time noninvasive imaging tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 42 publications
2
29
0
2
Order By: Relevance
“…As the mobility of water is restricted, the H 1 protons in water display lower motional frequencies, increasing the efficiency of the spin-lattice energy transfer which results in shorter T 1 times (Hashemi et al, 2010;Hills, 1998). In a number of studies, formation of a gel matrix has been shown to dramatically decrease relaxation times (Dobies, Kusmia, & Jurga, 2005;Fyfe & Blazek, 1997;Knorgen, Arndt, Richter, Kuckling, & Schneider, 2000;Oztop, Rosenberg, Rosenberg, McCarthy, & McCarthy, 2010). Thus, it is safe to conclude that the decrease in T 1 times due to gel formation was high enough to compensate for the effect of increasing moisture content.…”
Section: T 1 Relaxation Time Measurementsmentioning
confidence: 97%
See 1 more Smart Citation
“…As the mobility of water is restricted, the H 1 protons in water display lower motional frequencies, increasing the efficiency of the spin-lattice energy transfer which results in shorter T 1 times (Hashemi et al, 2010;Hills, 1998). In a number of studies, formation of a gel matrix has been shown to dramatically decrease relaxation times (Dobies, Kusmia, & Jurga, 2005;Fyfe & Blazek, 1997;Knorgen, Arndt, Richter, Kuckling, & Schneider, 2000;Oztop, Rosenberg, Rosenberg, McCarthy, & McCarthy, 2010). Thus, it is safe to conclude that the decrease in T 1 times due to gel formation was high enough to compensate for the effect of increasing moisture content.…”
Section: T 1 Relaxation Time Measurementsmentioning
confidence: 97%
“…The variations in relaxation spectrum can be used as an indicator for numerous proton related changes within food systems such as an increase in water content, proton exchange between compartments and physiological incidences that causes new protons pools to emerge (Belton & Capozzi, 2011;Ersus et al, 2010;Hills, 1998;Oztop et al, 2010). For living cells, these proton pools refer to water compartments within the cell (Belton & Capozzi, 2011;Ersus et al, 2010).…”
Section: D T 2 Relaxation Spectramentioning
confidence: 98%
“…Manganese chloride, a paramagnetic material, is used as a contrast agent in Magnetic Resonance Imaging experiments. The samples that incorporated manganese chloride were also used in a companion study (Oztop et al, 2010). Sodium azide (Sigma Chemical Co., St. Louis, MO, USA) was added at a concentration of 0.02% (w/w) to all protein solutions as an antimicrobial agent.…”
Section: Gel Preparationmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27] It consists of alternately placed monomers of D-glucuronic acid and N-acetyl-D-glucosamine linked by β-glycosidic bonds. [28,29] The water binding capacity, the time-scale and mechanism of water dynamics in the hyaluronic acid gels are factors determining the medical performance of dermal fillers. For medical use hyaluronic acid is often subjected to a cross-linking process that improves its rheological properties.…”
Section: Introductionmentioning
confidence: 99%